2016
DOI: 10.3934/publichealth.2016.4.781
|View full text |Cite
|
Sign up to set email alerts
|

Let the Children Play: Scoping Review on the Implementation and Use of Loose Parts for Promoting Physical Activity Participation

Abstract: Active play has become a critical focus in terms of physical activity participation in young children. Unstructured or child-led play offers children the opportunity to interact with the environment in a range of different ways. Unstructured materials, often called loose parts, encourage child-led play, and therefore may also promote physical activity. The purpose of this scoping review was to determine what is currently known about how loose parts may influence physical activity participation. Following a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 12 publications
2
32
0
5
Order By: Relevance
“…Quantitatively oriented outcomes for playtime interventions have been studied mostly with respect to physical activity (PA), and there is a growing and robust evidence base in this area (Dobbins, Husson, DeCorby, & LaRocca, 2013; Engelen et al, 2013; Houser, Roach, Stone, Turner, & Kirk, 2016; Ridgers, Carter, Stratton, & McKenzie, 2011). With respect to LPP interventions specifically, in a cluster-randomised trial of an LPP + parent education intervention, Engelen et al (2013) used accelerometer-based measures and found significant increases in step counts and minutes spent in moderate-vigorous physical activity (MPVA), as well as a decrease in sedentary behaviour in the intervention condition when compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitatively oriented outcomes for playtime interventions have been studied mostly with respect to physical activity (PA), and there is a growing and robust evidence base in this area (Dobbins, Husson, DeCorby, & LaRocca, 2013; Engelen et al, 2013; Houser, Roach, Stone, Turner, & Kirk, 2016; Ridgers, Carter, Stratton, & McKenzie, 2011). With respect to LPP interventions specifically, in a cluster-randomised trial of an LPP + parent education intervention, Engelen et al (2013) used accelerometer-based measures and found significant increases in step counts and minutes spent in moderate-vigorous physical activity (MPVA), as well as a decrease in sedentary behaviour in the intervention condition when compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…Violet noted the enjoyment that the unstructured play in the natural environment brings to the children who attend playgroup. Unstructured play, particularly in nature-based environments, brings many benefits to children in achieving a number of developmental milestones such as problem solving and coping with risk, as well as enjoyment (Houser, Roach, Stone, Turner and Kirk, 2016). Playing in the garden is part of a "continual production of places, place identity, and social memory" as memories are created and recreated in everyday places (Atkinson, 2007, p. 522).…”
Section: Playfulmentioning
confidence: 99%
“…While not advocating that the design of third places should provide opportunities for children to taunt each other, nor for adults to control behaviour through cruel plant selection, Matthew's recounting this story illustrates the freedom of activity in the community garden. In dense urban environments, there can be a lack of space left for unregulated activity and unstructured play (Houser et al, 2016).…”
Section: Home Away From Homementioning
confidence: 99%
“…An important consideration with loose parts is that the materials be open-ended, to allow for unstructured child-led play, and for children to make use of these materials any way they choose. Although the concept of loose parts has existed for many years [34], to the authors’ knowledge, no evidence exists on the efficacy of integrating loose parts materials in centres’ outdoor spaces as a means of improving children’s physical literacy and increasing PA and active outdoor play [36]. Considering the exploratory and open-ended nature of loose parts materials, it is possible that these materials could influence the basic aspects associated with physical literacy, including movement competence, confidence and motivation, and daily behaviors, increasing the likelihood of lifelong PA participation [30].…”
Section: Introductionmentioning
confidence: 99%